NEW METHOD TO PREDICT THE LIFE OF HIGH AND LOW CYCLE COMPOSITE FATIGUE LIFE (MT) - SHI HongMei; CUI Lu; HOU Wei; WANG Peng (Jixie qiangdu)
Engine, internal combustion engine, steam turbine rotors and other high-temperature components were often subjected to high and low cycle composite fatigue loads during operation. A new method by the curves of strain ratio(εHCF/εLCF)-life ratio(NLCF/HCF/NLCF) to predict the life of high and low cycle composite fatigue was advanced. The analysis of experimental data of three different materials showed that this method had certain versatility. The estimated values of life were within the error tolerance range by comparing the life estimation value with the experimental results, indicating that this method can better predict the life of high and low cycle composite fatigue for high temperature equipment materials.